Technologies for healthcare 4.0 from AI and IoT to blockchain - Ramamurthy, Karthik; Kulanthaivelu, Suganthi; Sagayam, Kulandairaj Martin; Dutta, Soumi 1992-; Paryati (Healthcare technologies series, 2023)
There are a growing number of challenges in handling medical data in order to provide an effective healthcare service in real-time. Bridging the gap between patient expectations and their experiences needs effective collaboration and connectivity across the healthcare ecosystem. The success of joined-up care relies on patient data being shared between all active stakeholders, including hospitals, outreach workers, and GPs. All these needs and challenges pave the way for the next trend of development in healthcare - healthcare 4.0. This book covers the state-of-the-art approaches in AI, IOT, cloud, big data, deep learning, and blockchain for building intelligent healthcare 4.0 systems, which provide effective healthcare services in real-time. The editors consider the benefits and challenges of immersive technologies and mixed reality systems for physical and mental health conditions, and outline and discuss the trending technologies supporting the internet of medical things, patient-centred care, assisted medical diagnoses, and electronic medical records. "Technologies for Healthcare 4.0: From AI and IoT to blockchain" is essential reading for researchers, scientists, engineers, designers and advanced students in the fields of computer science, computer vision, pattern recognition, machine learning, imaging, feature engineering, IOT, AI, signal processing, blockchain and big data for healthcare and those in adjacent fields